Clinico-epidemiological study on animal bite presenting to a tertiary care hospital in western part of Nepal - Pokhrel, Saroj; Yadav, Roshan; Sharma, Karuna; Shrestha, Abhishek; Poudel, Rekha; Pun, Chandra Bahadur (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Animal bite is a common public health problem and dog bites are most common among them in Nepal. Rabies infection is of most significant concern following animal-bites’ injuries. This study aimed to assess the epidemiological variation in terms of demographic variables, type of animal, circumstances of bite, type and site of wound and outcome of the animal bite.Methods: It was a descriptive cross-sectional study conducted at emergency department of Gandaki Medical College Teaching Hospital and Research Centre among animal-bite cases from October 1, 2020 to September 30, 2021 using a pre-designed questionnaire.Results: Out of total 217 cases of animal-bite included in the study, 65 (29.95%) were of 21 to 30 years and 129 (59.46%) were males, 120 (55.23%) cases hailed from rural area and 63 (29.03%) were farmers. Most cases 168 (77.42%) were bitten by dog among which 93 (55.35%) were owned dogs and only 22 dogs were vaccinated. A total of 127 (58.53%) were unprovoked and lower limb 130 (59.91%) was the commonest site. World Health Organization (WHO) Category II wound were the most commonly encountered 122 (56.22%). Majority 99 (45.62%) came to hospital within 25 to 48 hours of bite and after cleaning the wound site 115 (52.99%). Only 81 (37.78%) animals were observed for 10 days after the bite out of which 5 (6.09%) developed signs of rabies.Conclusions: Animal bite was common in males and source was owned dogs. Majority of the owned dogs were not vaccinated and most of the cases visited hospital without following first-aid measures.